Dynamics of the phytoplankton community of an Argentine Pampean wetland in relation to water environmental variables - Leonor Cony, Noelia; Cristina Ferrer, Nora; Jorge Cáceres, Eduardo (HIDROBIOLÓGICA, 2017)
Background. Shallow lakes are an essential component of the Argentine Pampean wetlands. The Sauce Grande shallow lake is a typical water body of the Argentine Pampean wetlands, based on its shallow characteristics and its homogeneity in terms of physical, chemical, and biological characteristics. Phytoplankton is dominant in the turbid shallow lake and is sensitive to internal fluctuations in the water body and prevailing environmental conditions that affect its abundance and distribution. Goals. We conducted a temporal and spatial analysis of the distribution and abundance of the phytoplankton community in the Sauce Grande shallow lake (province of Buenos Aires, Argentina), from April to September 2012, in order to study the influence of physicochemical variables of the water on phytoplankton. Methods. We undertook Cluster Analysis (CA), Principal Component Analyses (PCA) and Spearman correlations between the biotic and physicochemical variables recorded at two sites of the shallow lake. Results. The multivariate analysis showed that certain water physicochemical factors (conductivity, depth, pH, turbidity, and temperature) profoundly influenced the phytoplankton dynamics, giving rise to a seasonal succession of community species, with a clear dominance of Cyanobacteria. The Spearman correlation showed that Cyanobacteria relate positively and significantly to conductivity whereas Chlorophyta and Bacillariophyta relate negatively and significantly to temperature, pH, conductivity, and salinity. Chlorophyta was the group with the highest number of recorded taxa while Cyanobacteria constituted the largest group, the most abundant species being Synechocystis salina Wislouch. Conclusions. The results obtained in this study demonstrate that the phytoplankton community of the Sauce Grande shallow lake is highly susceptible to changes in water environmental conditions, in particular to water level fluctuations, and to conductivity, pH, and temperature.